Question #76bf7

1 Answer
Sep 9, 2017

2x^3sin^-1x - (2/3)sqrt(1-x^2)(x^2+2)2x3sin1x(23)1x2(x2+2)

Explanation:

integration by parts formula:
intu(dv)/dxudvdx = uv-int(vu')dx

So pick something you can integrate (v), and something you can differentiate (u)
u= sin^-1 x :. u' = 1/sqrt(1 - x^2
v=2x^3 because v' = 6x^2

then plug into the formula:

sin^-1x*2x^3 - int(2x^3)/sqrt(1-x^2)dx

(2x^3)/sqrt(1-x^2) is a product - can also write as 2x^3*(1-x^2)^(-1/2) so will need to use integration by parts again. This comes out as -(2/3)sqrt(1-x^2)(x^2+2)